Pink Salmon induce a trophic cascade in plankton populations in the southern Bering Sea and around the Aleutian Islands. (8th June 2018) - Batten, Sonia Dawn; Ruggerone, Gregory T.; Ortiz, Ivonne
Abstract: We examined the hypothesis of top‐down (predator) control of plankton populations around the Aleutian Islands and in the southern Bering Sea using a 15 year time series (2000–2014) of plankton populations sampled during summer by Continuous Plankton Recorders. Our analyses reveal opposing biennial patterns in abundances of large phytoplankton and copepods. This pattern is likely caused by the predation pressure on copepods from biennially abundant eastern Kamchatka Pink Salmon that results in a trophic cascade. In odd years, Pink Salmon are exceptionally abundant, large copepod abundance is low, and abundance of large diatoms grazed by copepods is high. Furthermore, large copepod abundance was inversely correlated, and diatom abundance was positively correlated, with Pink Salmon abundance. In addition to influencing the abundance of diatoms and large copepods we also report an effect on phytoplankton taxonomic composition. We find regional differences in the expression of these effects with alternating odd/even year patterns being strongest in the central Southern Bering Sea and eastern Aleutians and reduced, or absent, in the western Aleutians. When the abundance of 2013 Pink Salmon was unexpectedly low, there were consequent changes in the plankton populations, with highest recorded numbers in the time series of large copepods and microzooplankton (hard‐shelled ciliates). These findings emphasise the importance of variability in predator abundance and its effect across the ecosystem, which in this case was greater than physical oceanographic variability.